Tolerability and Efficacy of Multiple Series of Intravitreal Methotrexate Injections for Complex Retinal Detachment Associated with Proliferative Vitreoretinopathy - Tessnim R. Ahmad; Jay M. Stewart (MDPI AG, 2023)
In this study, we retrospectively reviewed the outcomes of patients treated with one or more series of intravitreal methotrexate (MTX) injections as a surgical adjunct for the prevention of recurrent rhegmatogenous retinal detachment (RRD) related to proliferative vitreoretinopathy (PVR). The study subjects were patients with primary or recurrent RRD associated with grade C PVR, who received one or more series of 9 intravitreal MTX injections. Each series consisted of a single intraoperative MTX injection and then 8 weekly postoperative MTX injections as an off-label surgical adjunct for the prevention of PVR. The primary outcome was the retinal reattachment rate. The secondary outcome was the incidence of treatment-limiting side effects. A total of 14 eyes of 14 patients were identified. The median age was 61 years (range: 9-83), and 43% of the patients were female. Most patients (64%) had a prior primary surgical failure. After one MTX series, 10 eyes (72%) were attached, and 8 (57%) were free of PVR at a median follow-up of 11 months (range: 2-14). All failures after a single MTX series were successfully treated with repeat surgery and a second (n = 4) or third (n = 1) MTX series, for the final reattachment and PVR-free rates of 100%. None of the patients experienced treatment-limiting side effects. Therefore, multiple series of MTX injections can be tolerated if indicated in cases of aggressive PVR threatening the retina.